Campaign optimisation - Rowson, Paul (Henry Stewart Talks, 2008)
Optimising a single campaign using a response model, Response and value models, Campaign optimisation explained, Treatments, Constraints, Objective function, Predictive models, Methods of resolving contention, Mathematical formulation, Campaign optimisation software, Business benefits of campaign optimisation